Tryptophan Dietary Impacts Gut Barrier and Metabolic Diseases - Taleb, Soraya (Frontiers in Immunology, 2019)
The intestine has a major role in the digestion and absorption of nutrients and gut barrier is the first defense line against harmful pathogens. Alteration of the intestinal barrier is associated with enhanced intestinal permeability and development of numerous pathological diseases including gastrointestinal and cardiometabolic diseases. Among the metabolites that play an important role within intestinal health, L Tryptophan (Trp) is one of the nine essential amino acids supplied by diet, whose metabolism appears as a key modulator of gut microbiota, with major impacts on physiological and pathological pathways. Recently, emerging evidence showed that the Trp catabolism through one major enzyme indoleamine 2, 3-dioxygenase 1 (IDO1) expressed by the host, affects Trp metabolism by gut microbiota to generate indole metabolites, thereby altering gut function and health in mice and humans. In this mini review, I summarize the most recent advances concerning the role of Trp metabolism in host-microbiota crosstalk in health and metabolic diseases. This novel aspect of IDO1 function in intestine will better explain its complex roles in a broad range of disease states where the gut function affects local as well as systemic health, and will open new therapeutic strategies.